The serially mediated relationship between emerging adults' social media use and mental well-being. (January 2020) - Rasmussen, Eric E.; Punyanunt-Carter, Narissra; LaFreniere, Jenna R.; Norman, Mary S.; Kimball, Thomas G.
Abstract: Social media use can negatively influence emerging adults' mental well-being. Therefore, this study explored the relation between social media use and mental well-being through difficulties with emotion regulation and perceived stress among a sample of U.S. college-student emerging adults. Results revealed that social media is indirectly related to mental health problems when emerging adults have difficulty with emotion regulation and perceived stress. The study also found that emerging adults' social media use is an outcome of difficulties with emotion regulation through the effect of these difficulties on perceived stress and mental well-being. Findings suggest that social media use may be a risk factor for mental health struggles among emerging adults, and that social media use may be an activity to which emerging adults resort when dealing with difficult emotions. Highlights: Social media use is related to mental health problems among emerging adults. Emerging adults use social media to deal with stress. Social media use may be a maladaptive way to deal with negative emotions.